Improvement of standard suspension type insulator by the semiconducting glaze for pollution condition - Samanmit, U.; Chusanapiputt, S.; Phoomvuthisarn, S.; Vassanasong, A.; Pinjom, A.; Pattanadech, N.; Yutthagowit, P.; Boonsaner, N. (My University, 2007)
This paper presents the behavior of 52-1 standard type suspension insulators coated with semiconducting glaze in some areas of the bottom side adjacent to the pin of insulators. Computer simulation program was carried out to investigate the electric field distribution of all tested insulators. The simulation results show that maximum electric field strength of semiconducting glaze insulators are decreased 3.13-26.26% compared with that of ordinary suspension insulators. Then the flashover voltage of the test specimen was investigated both dry and salt fog pollution condition according to IEC 507. The test results show that corona inception voltage of semiconducting glaze insulator is increased under artificial contamination test but its dry flashover voltage is decreased with increasing the semiconducting glaze length. It was found that the suitable length of semiconducting glazed standard insulator is 28 millimeters that has increasing corona inception voltage and flashover voltages are in the acceptable voltage rang of ANSI 52-1 standard. © 2007 RPS.
Keywords: Corona inception voltage; Flashover voltage; Semiconducting glaze; Suspension insulator